IMMIGRATION SUPERVISION ON SEA TRANSPORTATION IN THE IMMIGRATION EXAMINATION PLACE OF TANJUNG PERAK SEA PORT - Mangapul Alexus Simbolon (Jurnal Ilmiah Kajian Keimigrasian, 2021)
For the sake of realizing the upholding of state sovereignty and security, Indonesia must prioritize the duties and functions of Immigration in filtering people who want to enter or leave the territory of Indonesia by upholding the principle of Immigration, namely selective policy, especially for immigration officers at immigration checkpoints at airports, ports, and even at cross-border posts that must always prioritize this principle, that is, only foreigners who benefit and benefit the Indonesian state can enter Indonesian territory. Increased supervision of sea transportation means at the Tanjung Perak Seaport TPI must start from reforming the rules in carrying out immigration duties and functions by prioritizing immigration landing SOPs, regulation and availability of adequate budget preparation human resources as well as an increase in the welfare of officers in carrying out their duties both regarding the availability of equipment. transportation and accommodation outside the area. Permenkumham Number 44 of 2015 has not been implemented optimally, the old habits that have traditionally been in the landing task are still running. This mindset is clearly no longer appropriate to the current situation with rapid technological advances and is not in line with the Kemenkumhan Values, namely "PASTI".